2004
DOI: 10.1111/j.1745-6606.2004.tb00869.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Consumer Participation on Price Sensitivity

Abstract: This study examined the noneconomic factors affecting consumers’ participation in purchase decisions, focusing in particular on the social aspect of the buyer‐seller interaction. In addition, we attempted to clarify the association between consumer participation and price sensitivity. Of the four social dimensions of consumer participation—preparation, relationship building, information exchange, and intervention—our results indicated that the first three dimensions are negatively associated with price sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 23 publications
1
20
0
2
Order By: Relevance
“…If the emotional aspect is taken into account, a greater participation in purchasing can create bonds between customer and supplier (covering social or relational needs in the case of highly interactive goods or services), which could lead to a reduced price sensitivity of buyers (HSIEH et al, 2004).…”
Section: Frequency Of Purchasementioning
confidence: 99%
See 3 more Smart Citations
“…If the emotional aspect is taken into account, a greater participation in purchasing can create bonds between customer and supplier (covering social or relational needs in the case of highly interactive goods or services), which could lead to a reduced price sensitivity of buyers (HSIEH et al, 2004).…”
Section: Frequency Of Purchasementioning
confidence: 99%
“…Finally, it is noteworthy that although different research have found little or no relationship between demographic variables and price sensitivity (KIM et al, 1999), such factors should be included in studies in order to prevent potential interference in results (HSIEH et al, 2004).…”
Section: Socio-demographic Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Customer participation refers to the behavior and involvement in terms of the spirit and material aspects of customers in the process of accepting products or services [5]. Most scholars believe that customer participation can be divided into multiple dimensions, including mainly the customer's efforts and inputs in mental, intellectual, physical, emotional and other aspects [5,6]. To sum up, we can largely divide the customer participation into two major aspects of customer participation psychology and customer participation behavior, the customer participation psychology mainly refers to the psychological process of cognition and emotion [7], participation is the behavior commonly created value behavior through the cooperation with the relevant departments [8].…”
Section: Organization Participation In Place Brandingmentioning
confidence: 99%